Spiritual Entrepreneurship: Memaknai Spiritualitas Kerja Kristen - Ignatius Bambang Sukarno Hatta; Romi Lie (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2022)
The spirituality of work in secular circles is currently developing in such a way and mostly has a positive impact on the world of work itself, because of its nature which provides a balance between work and all its demands, with humans in their inner satisfaction and deepest desire to fulfill and serve the highest goals set forth. beyond existence. Efforts to explore the spirituality of Christian work have become an urgent need, not because they want to compete with the spirituality of work that is currently prevailing secularly, but as a form of fulfilling the Christian missionary call to "witness, preach the Gospel, make disciples of all nations." Apart from being an effort to fulfill the call of Christian mission, this also helps those who live the spirituality of Christian work to have a quality work ethic in their workplace, because they do it productively, independently and spiritually. Through the literature study method, it is concluded that spiritual entrepreneurship is found to be the right choice that can meet the criteria and forms of Christian work spirituality needed.AbstrakSpiritualitas kerja dikalangan sekuler saat ini berkembang sedemikian rupa dan kebanyakan memberikan dampak yang positif bagi dunia kerja itu sendiri, oleh karena sifatnya yang memberi keseimbangan antara kerja dan segala tuntutannya, dengan manusia di dalam kepuasan batin serta keinginan terdalamnya untuk memenuhi dan mengabdi pada tujuan tertinggi yang melampaui keberadaanya. Upaya menggali spiritualitas kerja Kristen menjadi sebuah kebutuhan yang mendesak dilakukan, bukan karena ingin menyaingi spiritualitas kerja yang saat ini sedang berlaku secara sekuler, melainkan sebagai bentuk pemenuhan panggilan misi orang Kristen untuk “menjadi saksi, memberitakan Injil, memuridkan segala bangsa.” Selain sebagai upaya pemenuhan panggilan misi Kristiani, hal ini turut membantu mereka yang menghidupi spiritualitas kerja Kristen untuk memiliki etos kerja berkualitas di tempat kerjanya, karena dikerjakannya secara produktif, mandiri dan rohani. Melalui metode studi kepustakaan maka disimpulkan bahwa entrepreneurship rohani di dapati sebagai pilihan tepat yang dapat memenuhi kriteria dan bentuk dari spiritualitas kerja Kristen yang dibutuhkan.